Implementation of Discipline and Responsibility Character Cultivation in Limited Face-to-Face Learning Systems in Elementary Schools - Chalid, Rio Idam (Program Magister Teknologi Pendidikan Universitas Jambi, 2017)
This research aims to describe the implementation of discipline and responsibility character education at SDN 99/X Sidomukti. This research is qualitative research with a phenomenological type. The research subjects were class IV teachers and class IV students at SDN 99/X Sidomukti. The object of this research is the implementation of discipline and responsibility character education. This research uses data collection techniques in the form of observation, interviews and documentation. Data analysis uses Miles and Huberman analysis techniques (data reduction, data display, and drawing conclusions). Test the validity of the data using triangulation of techniques and sources. The research results show that the implementation of discipline and responsibility character education at SDN 99/X Sidomukti includes three aspects, namely planning, implementation and evaluation. Planning is carried out by incorporating character education into the school curriculum and regulations. Implementation by integrating the character of discipline and responsibility in self-development activities, subjects and school culture. Evaluation is carried out by assessing student attitudes and conducting evaluations with the school principal, teachers and student guardians.